Chronic Ulcers in Thromboangiitis Obliterans (Buerger's Disease): Updating Epidemiology, Physiopathology, and Bosentan—A Novel Strategy of Therapy. (24th February 2013) - López de Maturana, Ignacio; Rodriguez, Javier; González, Carmen; Bleda, Silvia; de Haro, Joaquin; Acin, Francisco
Abstract : Thromboangiitis obliterans (TAO) or Buerger's disease is associated with both distal ulcers in the extremities and the possibility of amputation. The only treatment that has been shown to be effective in TAO is complete abstention from smoking. In spite of this, the disease progresses in up to 30 percent of cases and finally results in limb amputation. Only a few pharmacological and surgical options are available to date to improve healing ulcers in TAO. The efficacy of prostaglandin analogues is controversial. This paper summarizes the current evidence for medical treatment with bosentan in chronic ulcers in TAO patients. These available data up to date allow us to conclude that the beneficial effects of bosentan on improving endothelial function, inflammatory processes, and selective vasodilatation of damaged vessels result in a clinical enhancement regarding healing and preventive digital ulcers in such patients. In any case, these promising findings have to be confirmed with larger randomised trials.